Photoluminescence Emission and Raman Vibration Properties of Asymmetric Mn2+-Doped ZnO Nanoparticle Fabricated by a Solvothermal Method - Sang, Nguyen Xuan; Thi Phuong Anh, Nguyen; Duy Dung, Nguyen; Hoang Cao Huy, Nguyen; Huu Tho, Nguyen; Thi Lan Anh, Luu (VNU Journal of Science: Mathematics - Physics, 2019)
In this study, Mn 2+ -Doped ZnO nanoparticle with hexagonal wurtzite phase was fabricated by a solvothermal method where various contents of Mn ion were in situ -doped in ZnO nanostructure. The crystal structure and morphological properties of the nanoparticle were investigated by X-ray diffractometry, Raman spectroscopy and transmission electron microscopy. The photoluminescence (PL) measured at room temperature showed red-shift of near-band-to-band emission and the evolution of visible emissions in the doped samples. The study also analyzed the PL characteristics of synthesized samples and  revealed the role of dopant Mn 2+ to defect states of ZnO.